The answer should be p=-3
Answer: Choice C
h(x) = -x^4 + 2x^3 + 3x^2 + 4x + 5
===========================================
Explanation:
When reflecting the function f(x) over the y axis, we replace every x with -x and simplify like so
f(x) = -x^4 - 2x^3 + 3x^2 - 4x + 5
f(-x) = -(-x)^4 - 2(-x)^3 + 3(-x)^2 - 4(-x) + 5
f(-x) = -x^4 + 2x^3 + 3x^2 + 4x + 5
h(x) = -x^4 + 2x^3 + 3x^2 + 4x + 5
Note the sign changes that occur for the terms that have odd exponents (the terms -2x^3 and -4x become +2x^3 and +4x); while the even exponent terms keep the same sign.
The reason why we replace every x with -x is because of the examples mentioned below
-----------
Examples:
The point (1,2) moves to (-1,2) after a y axis reflection
Similarly, (-5,7) moves to (5,7) after a y axis reflection.
As you can see, the y coordinate stays the same but the x coordinate flips in sign from negative to positive or vice versa. This is the direct reason for the replacement of every x with -x.
Polynomial requirements
1. never divide by a placeholder
2. variable exponent has to be a whole number
3. can't have infinte terms
by 1. we eliinate 2nd one
by 2. we eliminate first one (√x=x^1/2) and 3rd one because it has an exponent in placeholder
thie leaves us with last one
f(x)=2x³-5x⁵-(2/9)x²+9
last one is answer
Answer:
I. 1000
w. 7 days
s. 35 days
n. 16
r. I don't know but maybe 5 1/3
g. 828.75
e. 24
H. 14
t. 36
l. I don't know
d. 6600
o. 90
50% i'm going to show you with=25%
you start a full calls
/4 going to the movies
]/3 like action movies
25%25% =50%